Graphic design discourse evolving theories, ideologies, and processes of visual communication - Kim, Henry Hongmin; Geissbühler, Steff (Princeton Architectural Press, 2017)
If the aim of graphic design is to communicate meaning clearly, there's an irony that the field itself has struggled between two contradictory opposites: rote design resulting from a rigorous, fixed set of rules, and eccentric design that expresses the hand of the artist but fails to communicate with its audience. But what if designers focused on process and critical analysis over visual outcome? Through a carefully selected collection of more than seventy-five seminal texts spanning centuries and bridging the disciplines of art, architecture, design history, philosophy, and cultural theory, Graphic Design Discourse: Evolving Theories, Ideologies, and Processes of Visual Communication establishes a new paradigm for graphic design methodologies for the twenty-first century. This illuminating anthology is essential reading for practicing designers, educators, and students trying to understand how to design in a singular, expressive way without forgoing clear and concise visual communication.